2009
DOI: 10.17221/1665-cjas
|View full text |Cite
|
Sign up to set email alerts
|

The use of bacterial inoculants for grass silage: their effects on nutrient composition and fermentation parameters in grass silages

Abstract: ABSTRACT:The effect of three microbial inoculants (Lactobacillus plantarum CCM 4000, L. fermentum LF2, and Enterococcus faecium CCM 4231) on the fermentation and nutritive value of orchard grass silage was studied under laboratory conditions. The first-cut orchard grass (280 g of dry matter/kg) was ensiled at 21°C for 105 days. All inoculants were applied at 1.0 × 10(9) CFU/ml. Uninoculated silage served as control. After inoculation, the chopped orchard grass was ensiled in 40 (1 l) plastic jars divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 25 publications
6
23
2
1
Order By: Relevance
“…The decrease of concentrations of LA and AA in silages from the first cut observed in our study was in agreement with the study by Váradyová et al (2013), where similar effects were reported from microbial inoculants compared to untreated silage of cocksfoot. Nevertheless, in the second cut, increased concentrations of these acids were observed; hence, our findings are consistent with studies reported by Jalč et al (2009) once more on cocksfoot.…”
Section: Chemical Composition Of Green Foragesupporting
confidence: 93%
See 2 more Smart Citations
“…The decrease of concentrations of LA and AA in silages from the first cut observed in our study was in agreement with the study by Váradyová et al (2013), where similar effects were reported from microbial inoculants compared to untreated silage of cocksfoot. Nevertheless, in the second cut, increased concentrations of these acids were observed; hence, our findings are consistent with studies reported by Jalč et al (2009) once more on cocksfoot.…”
Section: Chemical Composition Of Green Foragesupporting
confidence: 93%
“…These findings are consistent with the study realized by Jalč et al (2009), where the content of NDF in cocksfoot silage tion activity associated with catabolism of cellulose and hemicellulose in inoculated forage grasses. In accordance with different findings, the DM losses of up to 12% are considered a reliable indicator of inoculant activity in silages forage (Driehuis et al, 2001).…”
Section: Chemical Composition Of Green Foragesupporting
confidence: 93%
See 1 more Smart Citation
“…The lactic acid : acetic acid ratio is a good efficiency indicator for silage fermentation (Jalc et al 2009). This ratio ideally should not be less than 3 : 1, and the higher it is the better (Kung and Shaver 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Most commercially available inoculants contain homofermentative LAB, which are used with the objective of stimulating the rate and extent of fermentation so that either the concentration or the proportion of lactic acid in the total fermentation acids in the silage is as high as possible (Jalc et al 2009;Wilkinson and Davies 2013).…”
Section: Doi: 1017221/67/2016-cjasmentioning
confidence: 99%